Egg Production Performance and Prediction of Standard Limits for Traits of Economic Importance in Broiler Breeders - Ali, Murad; Farooq, M.; Durrani, F.R.; Chand, N.; Sarbiland, K.; Riaz, A. (International Journal of Poultry Science, 2003)
The present study was conducted on broiler breeders maintained in 24 different farms located in Mansehra and Abbotabad to investigate egg production performance and develop standard limits for production traits of economic importance. Average number of day-old chicks received at a broiler breeder farm was 19076.29, out of which 16449.08 birds attained sexual maturity and were housed in laying houses. Total hens housed represented 14037.32 females and 1559.70 males (a male to female ratio of 1:9). Reserved male stock (852.06 birds) was 5.18% of the total population. Average mortality during 323.46 days of growth and production period was 13.77%, representing 2.97, 4.99 and 5.81% mortality during brooding, growing and laying periods, respectively. Average age at point-of-lay, age at peak-of-lay and egg laying period were 164.67, 232.83 and 155.46 days. Age at point-of-lay (r = 0.227) and age at peak-of-lay (r = 0.333) were found positively but non-significantly correlated with total mortality in a flock. On the other hand flock size was found negatively correlated with age at point (r = -0.052) and age at peak-of lay (r = -0.415; p